2009
DOI: 10.1071/sr07054
|View full text |Cite
|
Sign up to set email alerts
|

Impact of soil conditions on hydrology and water quality for a brown clay in the north-eastern cereal zone of Australia

Abstract: Abstract. Hydrology and water quality impacts of alternative land management practices are poorly quantified for semi-arid environments in the northern Australia cropping zone, yet wide-scale changes in tillage practices and land use were being recommended based on experience from other environments.The objective of this study was to explore changes in soil profile and catchment hydrology and water quality associated with different soil surface conditions created by different tillage and grazing practices. Soi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Erosion studies in grain cropping lands (Freebairn et al, 2009) have demonstrated the importance of soil type and conditions of erosion rates. Murphy et al (in press) showed that considerable quantities of sediment, nutrient (from fertiliser) and herbicides (in this case metolachlor) can be lost under conventional management in dryland grain cropping.…”
Section: New Management Practices and Their Effectivenessmentioning
confidence: 99%
“…Erosion studies in grain cropping lands (Freebairn et al, 2009) have demonstrated the importance of soil type and conditions of erosion rates. Murphy et al (in press) showed that considerable quantities of sediment, nutrient (from fertiliser) and herbicides (in this case metolachlor) can be lost under conventional management in dryland grain cropping.…”
Section: New Management Practices and Their Effectivenessmentioning
confidence: 99%
“…Sediment losses from agricultural areas are commonly attributed to arable practices (Walling et al, 1999;Wass and Leeks, 1999;Freebairn et al, 2009;Van Oost et al, 2009;Duvert et al, 2010), especially where bare or freshly tilled soils are exposed to rainfall-runoff processes (Regan et al, 2012). Arable farming typically involves the mechanical redistribution of soil through ploughing and seed bed preparation, and via erosion from compacted and/or bare fields and down-slope tramlines (Chambers and Garwood, 2000;Withers et al, 2006;Boardman et al, 2009;Silgram et al, 2010;Regan et al, 2012;Soane et al, 2012).…”
Section: S C Sherriff Et Al: Suspended Sediment Dynamics In Agricumentioning
confidence: 99%
“…The current results on other components, for example soil evaporation (66% of fallow rainfall, results not shown elsewhere), also agree with similar studies (e.g. Silburn et al ., ; Thornton et al ., ; Freebairn et al ., ; Robinson et al ., ) that found soil evaporation at 65–73% of fallow rainfall.…”
Section: Resultsmentioning
confidence: 98%